International Environmental Governance: Lessons From Unea And Perspectives On The Post-2015 Era - Nyangon, Joseph (Journal of Sustainable Development Law and Policy, 2025)
The inaugural meeting of the United Nations Environment Assembly (UNEA) held in June 2014 in Nairobi, was a culmination of more than four decades of environmental governance since the United Nations Environment Programme (UNEP) was established in 1972 in Stockholm. The meeting addressed weighty and contentious issues including strengthening of UNEP’s role in promoting environmental governance and enhancing science-policy interface. Yet despite the historical significance of the meeting following universalization of the governing body of UNEP and current debates on the post-2015 development agenda, questions persist about the role of UNEP, its establishment, performance, and fragmentation of programmes and secretariats of the multilateral environmental agreements associated with it. This paper reviews the outcome of the inaugural UNEA session, while developing a political economy account of institutional arrangements of international environmental governance to clarify the potential for, and barriers to effective environmental reform. Multilaterally, international environmental governance continues to exhibit elements of complexity, fragmentation, lack of coordination as well as redundancy. In more critical terms, lack of policy integration between environmental regimes is a concern of environmental governance that the new UNEA should address as a matter of priority. Furthermore, incoherent policy objectives in international environmental law often characterised as a governance patchwork have been criticized for their economic orthodoxies that only serve to marginalize and delegitimize alternative modes of environmental governance. In this regard, a core part of UNEA’s institutional legitimacy depends on its success in coevolving to keep up with environmental challenges as they themselves change, as well as enhancing consensus-based stakeholder engagement, perspectives, and participation on environmental governance. This will be its true litmus test on how it responds coherently and effectively to international environmental governance in a post-2015 development world.